Optical properties of nanostructured semiconductors grown by MBE on non-conventional GaAs substrates - Khatab, Almontaser bellah Fathy (2014)
This thesis reports the optical properties of InAlAs QDs and InGaAsN QWs grown by Molecular Beam Epitaxy (MBE) on both the conventional (100) and high Miller index surfaces. InAlAs QDs on AlGaAs matrix are grown by MBE on the conventional (100) and non-(100) GaAs substrates using different growth conditions, namely, growth temperature, different confinement barriers, and amount of deposited material. PL measurements revealed differences in the optical properties that are caused by substrate orientation effects. The PL emission energies of QDs grown on high Miller index surfaces such as (311)A and (311)B are found to be strongly dependent on the atomic terminated surface [A (Ga face) or B (As face)] of the substrate. The QDs grown on (311)B plane show superior optical properties over QDs grown on (311)A and (100) planes. The optimum structure to achieve the highest optical efficiency of QDs emitting in the visible red part of electromagnetic spectrum ( ̴ 666 nm) consisted of 4.4MLs Al0.35In0.65As/Al0.45Ga0.55As QDs grown on (311)B plane at a growth temperature of 550 0C. In addition, a further investigation was carried out to study the effect of post-growth thermal annealing on the optical properties of InAlAs QDs grown on (100), (311)A, and (311)B planes. A noticeable enhancement of the PL intensity at 10 K for all planes was observed by increasing the annealing temperature up to 700 0C. Thermal annealing of (311)A InAlAs/GaAlAs QDs resulted in a negligible blue shift, while a large blue shift was observed from (311)B and (100) QDs. This is explained by the smaller size of QDs, smaller strain, and lower In segregation from (311)A GaAs orientation. PL and Transmission Electron Microscopy (TEM) have been used to investigate the optical and structural properties, respectively, of In0.36Ga0.64As1-yNy/GaAs double quantum wells (QWs) grown both on the conventional (100) and non-(100) GaAs substrates. These include In0.36Ga0.64As1-yNy/GaAs QWs with three different compositions of nitrogen, namely, 0%, 1%, and 2%. QWs grown on (311)A GaAs plane show higher nitrogen incorporation over all the other planes. TEM measurements show that (311)B QWs have inferior structural properties than QWs grown on (311)A and (100). TEM images demonstrated that the (311)B QWs interfaces are undulated and not uniform. In contrast QWs grown on (311)A and (100) display very uniform and very flat interfaces. The effect of thermal annealing on the optical properties of In0.36Ga0.64As1-yNy/GaAs double QWs grown on different planes was investigated for two sets of samples having 0% and 1% nitrogen. It was found that annealing at 700 0C for 30 seconds is the optimum annealing temperature which improves the PL efficiency for all QWs. The PL enhancement is larger in samples with 1% nitrogen than 0%.